Faktor Sosial dan Psikologis Terhadap Kemampuan BerbicaraBahasa Arab : Studi Kasus pada Santri Kelas 4 IntensifPondok Modern Daarul Hikmah Tangerang Tahun Ajaran 2023/2024 - Ummu Salamah; Imroatus Sholihah; Ahmad Royani (Institut Muslim Cendekia, 2025)
This research examines social and psychological factors on the ability to speak Arabic. The object of this research is the 4th grade students of the Intensive Pondok Modern Daarul Hikmah Tangerang. The aim of this research is to find out how social and psychological factors influence the ability to speak Arabic. The research method uses case studies with qualitative descriptive research, with data collection techniques; observation, interviews, and documentation. The results of data analysis state that there is a relationship between social and psychological factors on the ability to speak Arabic.